RAGAM BAHASA PRESENTER INSERT DI STASIUN TV TRANS TV - Santi Andriyani (Universitas Islam Nahdlatul Ulama Jepara)
The article is aimed at describing the use of language varieties used by presenters of infotainment Trans TV named Insert . This study describes the speech based on the word choices and the word accuracy. This study uses Descriptive Method. The collection of the data uses recording technique. The subjects of this study are the presenters of Insert in Trans TV. The findings of the study are, (1) variety of language used by the presenter infotainment Insert in Trans TV is casual, and (2) appropriate selection of words seen by the words of his own creation, and foreign words. Keywords: Ragam bahasa, bahasa santai, presenter Insert Trans TV